Submicroscopic and Asymptomatic Plasmodium Parasitaemia Associated with Significant Risk of Anaemia in Papua, Indonesia - Pava, Z; Burdam, F; Handayuni, I; Trianty, L; Utami, R; Tirta, Y; Kenangalem, E; Lampah, D; Kusuma, A; Wirjanata, G; Kho, S; Simpson, J; et al. (Public Library of Science, 2016)
Submicroscopic Plasmodium infections are an important parasite reservoir, but their clinical relevance is poorly defined. A cross-sectional household survey was conducted in southern Papua, Indonesia, using cluster random sampling. Data were recorded using a standardized questionnaire. Blood samples were collected for haemoglobin measurement. Plasmodium parasitaemia was determined by blood film microscopy and PCR. Between April and July 2013, 800 households and 2,830 individuals were surveyed. Peripheral parasitaemia was detected in 37.7% (968/2,567) of individuals, 36.8% (357) of whom were identified by blood film examination. Overall the prevalence of P. falciparum parasitaemia was 15.4% (396/2567) and that of P. vivax 18.3% (471/2567). In parasitaemic individuals, submicroscopic infection was significantly more likely in adults (adjusted odds ratio (AOR): 3.82 [95%CI: 2.49-5.86], p<0.001) compared to children, females (AOR = 1.41 [1.07-1.86], p = 0.013), individuals not sleeping under a bednet (AOR = 1.4 [1.0-1.8], p = 0.035), and being afebrile (AOR = 3.2 [1.49-6.93], p = 0.003). The risk of anaemia (according to WHO guidelines) was 32.8% and significantly increased in those with asymptomatic parasitaemia (AOR 2.9 [95% 2.1-4.0], p = 0.007), and submicroscopic P. falciparum infections (AOR 2.5 [95% 1.7-3.6], p = 0.002). Asymptomatic and submicroscopic infections in this area co-endemic for P. falciparum and P. vivax constitute two thirds of detectable parasitaemia and are associated with a high risk of anaemia. Novel public health strategies are needed to detect and eliminate these parasite reservoirs, for the benefit both of the patient and the community.